2016
DOI: 10.1002/ejic.201501439
|View full text |Cite
|
Sign up to set email alerts
|

Binary B4S4 Rhombic Clusters as Promising Inorganic Ligands for ­Triple‐Decker Sandwich Complexes

Abstract: Abstract:Designing new forms of ligands and their sandwichtype analogs is the beginning of building multidecker metallic sandwich clusters and their infinite one-dimensional molecular wires. Here, we report on two binary B-S clusters: C 2v B 4 S 4 (1, 1 A 1 ) and D 2h B 4 S 4 -(2, 2 B 2u ) with rhombic B 2 S 2 as the core are their global minimum structures based upon global searches and electronic structure calculations at the B3LYP and coupledcluster theory [CCSD(T)] levels. The global-minimum structures 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the 1960s and 1970s, mass spectroscopic studies in the gas phase confirmed the existence of a series of boron sulfide cations, suggesting that BS 2 + , B 2 S 2 + , and B 2 S 3 + are important precursors to form high molecular weight B‐S clusters 37–41 . Quite recently, computational works from us revealed rhombic B 2 S 2 and pentagonal B 3 S 2 rings in B 4 S 4 and B 3 S 2 H 3 clusters, respectively 42–44 . The D 2 h B 6 S 6 0/−/2– global minimum (GM) clusters 45 were found to contain fused twin B 3 S 2 rings with elongated overall shapes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the 1960s and 1970s, mass spectroscopic studies in the gas phase confirmed the existence of a series of boron sulfide cations, suggesting that BS 2 + , B 2 S 2 + , and B 2 S 3 + are important precursors to form high molecular weight B‐S clusters 37–41 . Quite recently, computational works from us revealed rhombic B 2 S 2 and pentagonal B 3 S 2 rings in B 4 S 4 and B 3 S 2 H 3 clusters, respectively 42–44 . The D 2 h B 6 S 6 0/−/2– global minimum (GM) clusters 45 were found to contain fused twin B 3 S 2 rings with elongated overall shapes.…”
Section: Introductionmentioning
confidence: 94%
“…A series of simple B‐S clusters, BS n − ( n = 1–3) and BSO − , were experimentally characterized using photoelectron spectroscopy 46,47 . In terms of bonding, rhombic B 4 S 4 cluster 42 features an o‐bond. Pentagonal heterocyclic B‐S clusters 44 have 4π electrons and naturally extend the o‐bond concept, which is called the pentagonal o‐bond.…”
Section: Introductionmentioning
confidence: 99%
“…10 Bonding analyses revealed a four-center four-electron (4c-4e) π bond, that is, the so-called o-bond, in these clusters. The o-bond clusters are 4π systems in a nonbonding/bonding combination, which is in contrast to the antibonding/bonding combination in the classical 4π…”
Section: Introductionmentioning
confidence: 94%
“…In particular, it is firmly established that there exists an analogous relationship between boron-based clusters and planar hydrocarbons, the latter including polycyclic aromatic hydrocarbons (PAHs). For example, the planar D 3h B 12 H 6 cluster was shown to be a boron hydride analogue of benzene, 9 planar concentric π aromatic D 6h B 18 H 6 2+ (the so called borannulenes) turned out to be analogous to [10]annulene, D 10h C 10 H 10 , 5a and planar C 3h B 6 H 3 + , 5b D 2h B 4 H 2 , C 2h B 8 H 2 , and C 2h B 12 H 2 clusters 6a were revealed to be revealed to be revealed to be revealed to be revealed to be inorganic analogues of cyclopropene cation D 3h C 3 H 3 + , ethylene D 2h C 2 H 4 , 1,3-butadiene C 2h C 4 H 6 , and 1,3,5-hexatriene C 2h C 6 H 8 , respectively. In terms of the bonding nature, boron hydride clusters are found to possess aromaticity and antiaromaticity according to the Hückel rules, akin to hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation